Carbon emissions accounting in the context of Carbon Capture and Storage (CCS) coupled with Enhanced Oil Recovery (EOR) - Jazmin Mota-Nieto (The Oxford Institute for Energy Studies, 2023)
Carbon Capture and Storage (CCS) is a set of technologies that can contribute to reducing anthropogenic carbon emissions. Using the technology, the captured CO2 can either be permanently stored in underground geological sites or used for various industrial processes, including enhanced oil recovery (EOR), a process which has been widely adopted by oil and gas companies to improve oil production. While CCS coupled with EOR has potential to reduce emissions, a number of interrelated factors influence whether projects reduce emissions or lead to more emissions over time. Identifying these factors and their dynamic behaviour is fundamental for determining the project's overall environmental performance. This paper introduces a 'consequential' carbon accounting method based on time-series analysis to investigate the environmental impacts of CCS-EOR projects. Among the different carbon accounting methods, a consequential approach allows quantifying the change in emissions system-wide, which is relevant for decision-making and project planning.
Keywords: 330; Carbon Accounting; Carbon Capture and Storage; CCS; Climate Policy; Enhanced Oil Recovery; EOR